(3QSGdI aj HjY GdhaGA hCMcGegs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; gPg GdeSGFd JJYdb HHjY GdhaGA PcQ TjN GdESdGe GdEeGe GdCLd fLe GdfSaj aj aJGhGg Cf GdHjY GdPj JYGQa Cgd ReGffG MjK dG ddQHhG hSehG HjY GdhaGAs
(3BNQgG (B:s
(3hbGd GHf CHj djdi dG JbHd GdHjfI HYO Gdjejf ef COH GdbGVj ddNUGas
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3Gdabg GdMfHdjs